An analytical study on the effective dimensions of leadership styles for enhancing organizational performance - Fariz, Fariz; Winarsih, Tutik (Indonesia Auditing Research Journal, 2024)
Leadership style plays an important role in improving organizational performance, especially in the face of increasingly complex global competitive challenges. Effective leadership is considered capable of increasing motivation, job satisfaction, and team cohesion, which ultimately contributes positively to organizational performance. The aim of this research is to examine the impact that different leadership styles, with a focus on transformational leadership, have on the results of an organization.  The research method used was a literature review of relevant scholarly sources, including articles, conference proceedings, and books that discuss the contribution of leadership style to organizational performance. Data collection was conducted through online database searches, including Google Scholar and JSTOR. The findings indicate that by promoting employee involvement and fostering a culture of constant enhancement, transformational leadership can greatly enhance organizational effectiveness. At the same time, transactional leadership may be successful in reaching short-term goals but lacks the ability to inspire lasting motivation. On the other hand, passive-avoidant leadership often results in hindered team dynamics and reduced productivity. The advice given in this research suggests that companies should focus on implementing transformational leadership in order to boost employee motivation, involvement, and creativity. Moreover, utilizing a blend of transformational and transactional leadership techniques may be effective in reaching both immediate and long-lasting objectives. Organizations are also advised to develop leadership competencies through training, as well as avoid passive-avoidant leadership styles that can be detrimental to team performance